A cento anni dalla Grande Guerra. Vol. 1 Il suicidio dell'Europa - Ferraris, Luigi Vittorio (Atti, 2017)
The volumes on the Great War that are here published are the result of a series of seminars held at the Department of Political and Social Sciences of the University of Florence between 2014 and 2015. Starting from the occasion of the centennial, the authors wanted to take stock of some specific aspects of the studies related to the First World War. To this purpose, historians, military analysts, political scientists and sociologists have questioned the meaning of the fracture that marks the beginning of the twentieth century and, consequently, the basic aspects of the new policy of the "short century", from both an Italian and European perspective.